Obstructive Sleep Apnea Monocytes Exhibit High Levels of Vascular Endothelial Growth Factor Secretion, Augmenting Tumor Progression - Carolina Cubillos-Zapata; Enrique Hernández-Jiménez; José Avendaño-Ortiz; Victor Toledano; Anibal Varela-Serrano; Isabel Fernández-Navarro; Raquel Casitas; Carlos Carpio; Luis A. Aguirre; Francisco García-Río; Eduardo López-Collazo (Mediators of Inflammation)
Obstructive sleep apnea (OSA) is a syndrome characterized by repeated pauses in breathing induced by a partial or complete collapse of the upper airways during sleep. Intermittent hypoxia (IH), a hallmark characteristic of OSA, has been proposed to be a major determinant of cancer development, and patients with OSA are at a higher risk of tumors. Both OSA and healthy monocytes have been found to show enhanced HIF1α expression under IH. Moreover, these cells under IH polarize toward a tumor-promoting phenotype in a HIF1α-dependent manner and influence tumor growth via vascular endothelial growth factor (VEGF). Monocytes from patients with OSA increased the tumor-induced microenvironment and exhibited an impaired cytotoxicity in a 3D tumor in vitro model as a result of the increased HIF1α secretion. Adequate oxygen restoration both in vivo (under continuous positive airway pressure treatment, CPAP) and in vitro leads the monocytes to revert the tumor-promoting phenotype, demonstrating the plasticity of the innate immune system and the oxygen recovery relevance in this context.